Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. - Echevarría-Zomeño, Sira; Ariza, David; Jorge, Inmaculada; Lenz, Christof; Del Campo, Antonio; Jorrín, Jesús V.; Navarro, Rafael M. (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.
The following values have no corresponding Zotero field: accession-num: 18778874
Keywords: Drought stress; Holm oak proteome; Mass spectrometry; Quercus ilex

Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.

Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.

The Holm Oak leaf proteome: Analytical and biological variability in the protein expression level assessed by 2-DE and protein identification tandem mass spectrometry de novo sequencing and sequence similarity searching (PROTEOMICS, 2005)
As a first approach in establishing the holm oak leaf proteome, we have optimised a protocol for this plant and tissue which includes the following steps: trichloroacetic acid-acetone extraction, two-dimensional gel electrophoresis (2-DE) on pH 5 to 8 linear gradient immobilised pH gradient strips as the first dimension, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis on 13% polyacrylamide gels as the second one. Proteins were detected by Coomassie staining. Gel images were recorded and digitalized, and the protein spots quantified by using a linear regression equation of protein quantity on spot volume obtained against standard proteins. Analytical variance was calculated for one-hundred protein spots from three replicate 2-DE gels of the same protein extract. Biological variance was determined for the same protein spots from independent tissue extracts corresponding to leaves from different trees, or the same tree at different orientations or sampling times during a day. Values of 26% for the analytical variance and 58.6% for the biological variance among independent trees were obtained. These values provide a quantified and statistical basis for the evaluation of protein expression changes in comparative proteomic investigations with this species. A representative set of the major proteins, covering the isoelectric point range of 5 to 8 and the relative molecular massr range of 14 to 78 kDa, were subjected to liquid chromatography-tandem mass spectrometry analysis. Due to the absence of Quercus DNA or protein sequence databases, a method based on the procedure reported by Liska and Shevchenko [1] including de novo sequencing and BLAST similarity searching against other plant species databases was used for protein identification. Out of 43 analysed spots, 35 were positively identified. The identified proteins mainly corresponded to enzymes involved in photosynthesis and energetic metabolism, with a significant number corresponding to RubisCO.